Uji Performansi Desain Terintegrasi Tungku Biomassa dan Penukar Panas - Muhammad Tahir; Rahmiaty Kasim; Yoyanda Bait (agriTECH, 2013)
A series testing of the integrated design of biomass furnace and heat exchanger was conducted to see the performance using methods such as the effectivenes-number of transfer unit (e-NTU),  the efficiency as a function of Fin Analogy Number (h(Fa)) and the log-mean temperature difference (LMTD). The biomass furnace as a plant to generated heat produced value of energy 25,600W with the burning rated of corncob 7.03 kg/hour. The calculation of amount of heat transfer to the cold fluid in the tubes as function of fluid characteristic, mass rated of dry air in a longitudinal section was 11,285W. The effectivenes as the ratio of actual heat transfered to the absolute maximum heat that can be transferred in a heat exchanger was 0.90. The efficiency of heat exchanger as a clear measurement of performance system was 0.78. The efficiency as a function of fin analogy number, employed several variable as it function; such as the product of UA, minimum heat capacity rate (Cmin) and the capacity ratio (Cr). Another performance showed by correction factor with value of 0.5 indicated that the heat exchanger was not a pure of counter-flow but made of cross-flow in the single segmental baffle with turbulances pattern (Re: 8.524 > 6.000).ABSTRAKSerangkaian pengujian terhadap desain terintegrasi tungku biomassa dan penukar panas telah dilakukan untuk melihat performansinya menggunakan metode efektifitas-NTU (e-NTU), efisiensi sebagai fungsi dari fin analogy number (h(Fa)) dan beda temperatur rata-rata logaritmik (LMTD). Tungku biomassa sebagai pembangkit panas menghasilkan energi senilai 25.600W dengan laju pembakaran tongkol jagung 7.03 kg/jam. Perhitungan laju pindah panas ke fluida dingin dalam pipa sebagai fungsi dari karakteristik udara, laju massa melalui luas penampang laluan diperoleh sebesar 11,285W. Efektivitas sebagai rasio laju pindah panas aktual dengan panas maksimum yang dapat dipindahkan dalam sebuah penukar panas diperoleh sebesar 0,90. Efisiensi penukar panas sebagai ukuran jelas performansi sistem diperoleh sebesar 0,78. Efisiensi dalam hal ini adalah fungsi dari fin analogy number sedangkan fin analogy number merupakan fungsi dari beberapa variabel seperti hasil perkalian UA, laju kapasitas panas minimum (Cmin) dan rasio kapasitas (Cr). Performansi lainnya ditunjukkan melalui nilai faktor koreksi sebesar 0,5 menunjukkan bahwa penukar panas tidak sepenuhnya merupakan aliran-melawan melainkan terbentuk aliran-silang khususnya di dalam ruang antar sekat dengan pola turbulensi (Re: 8.524 > 6.000).